2013
DOI: 10.1103/physrevlett.110.187802
|View full text |Cite
|
Sign up to set email alerts
|

Active Shape-Morphing Elastomeric Colloids in Short-Pitch Cholesteric Liquid Crystals

Abstract: Active elastomeric liquid crystal particles with initial cylindrical shapes are obtained by means of soft lithography and polymerization in a strong magnetic field. Gold nanocrystals infiltrated into these particles mediate energy transfer from laser light to heat, so that the inherent coupling between the temperature-dependent order and shape allows for dynamic morphing of these particles and well-controlled stable shapes. Continuous changes of particle shapes are followed by their spontaneous realignment and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 41 publications
1
41
0
Order By: Relevance
“…This class of systems also encompasses synthetic objects that actively shape the medium in which they are confined. The latter include liquid crystal colloids endowed with a tunable degree of freedom [18], whose interactions have been experimentally explored [19] with a view to controling self-assembly at the micrometer scale.…”
Section: Introductionmentioning
confidence: 99%
“…This class of systems also encompasses synthetic objects that actively shape the medium in which they are confined. The latter include liquid crystal colloids endowed with a tunable degree of freedom [18], whose interactions have been experimentally explored [19] with a view to controling self-assembly at the micrometer scale.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies also showed the importance of size [18][19][20][21][22][23][24] and shape [24][25][26][27][28][29][30][31] in elastic interactions and ensuing assemblies of colloidal particles in nematics. On the other hand, colloidal dispersions in twisted nematic and cholesteric LCs (CLCs) have received less attention [32][33][34][35][36][37][38][39][40][41][42][43][44] because of the complexity of the problem caused by, for example, the screening of elastic interactions by periodic structure of cholesterics. 44 This complexity increases as the ratio between the particle's size and cholesteric periodicity increases.…”
Section: Introductionmentioning
confidence: 99%
“…Particles shaped as letters of the Latin alphabet (Figure 7k,l), on the other hand, exhibit well-defined orientations with respect to n 0 and induce surface boojums with  i s i =correlated with their shapes. Other colloidal shapes studied recently include pyramids, spirals, shape-morphing elastomeric rods, gourd-shaped dimers, particles with nanoscale surface roughness, and so on (98)(99)(100)(101)(102)(103)(104)(105)(106)(107)(108)(109)(110)(111)(112)(113), in all cases demonstrating that the geometric shape pre-defines locations of topological defects and colloidal interactions. Facile control of nanoparticle and molecular organization and the ensuing composite properties can be achieved by applying electric, magnetic, and optical fields (80).…”
mentioning
confidence: 99%